Physiological responses of pacu (Piaractus mesopotamicus) to intermittent cold exposure: A comprehensive analysis of stress, immunity, antioxidant, and metabolic adaptations - de Fátima Pereira de Faria, Camila [UNESP]; de Andrade, Beatriz Ullian [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Springer Nature, 2025)
This study examined the energy-dependent physiological responses, including stress, innate immune, and antioxidant systems, as well as indicators of energy mobilization, in pacu (Piaractus mesopotamicus) exposed to intermittent cold, aiming to assess the correlations between these responses. The fish were acclimated to 28 °C, divided into two groups, a control group maintained at 28 °C, and another exposed to 16 °C for two 24 h periods with a 5-day interval between them. The fish were sampled at six time points: baseline (after acclimatization to 28 °C), 24 h after the 1st exposure to 16 °C, after 5 days of recovery at 28 °C, 24 h after the 2nd exposure to 16 °C, and after 24 and 48 h of recovery at 28 °C. The reduction in temperature activated the stress response, the innate immune system, and the antioxidative system as well as mobilized lipids from the visceral stores and preserved the circulating levels of triglycerides. Intermittent exposure of fish to cold increased plasma cortisol after both exposures, activated leukocyte respiratory activity after the 2nd exposure, and triggered the compensatory lysozyme response after temperature recovery in both cold exposures in addition to increasing the number of circulating monocytes and granulocytes. The activity of the enzymes catalase (CAT) and superoxide dismutase (SOD) increased after the 1st and 2nd cold exposures, respectively. Glutathione peroxidase (GPx) activity increased after the 2nd exposure compared to the control. The subtropical fish pacu was sensitive to intermittent cold exposure and was able to display protective physiological responses.
Keywords: Antioxidant system; Cortisol; Immune system; Oxidative stress; Temperature change